Quinazoline Derivatives as Potential Therapeutic Agents in Urinary Bladder Cancer Therapy - Wdowiak, Paulina; Matysiak, Joanna; Kuszta, Piotr; Czarnek, Katarzyna; Niezabitowska, Ewa; Baj, Tomasz (Frontiers in Chemistry, 2021)
Cancer diseases remain major health problems in the world despite significant developments in diagnostic methods and medications. Many of the conventional therapies, however, have limitations due to multidrug resistance or severe side effects. Bladder cancer is a complex disorder, and can be classified according to its diverse genetic backgrounds and clinical features. A very promising direction in bladder cancer treatment is targeted therapy directed at specific molecular pathways. Derivatives of quinazolines constitute a large group of chemicals with a wide range of biological properties, and many quinazoline derivatives are approved for antitumor clinical use, e.g.,: erlotinib, gefitinib, afatinib, lapatinib, and vandetanib. The character of these depends mostly on the properties of the substituents and their presence and position on one of the cyclic compounds. Today, new quinazoline-based compounds are being designed and synthesized as potential drugs of anticancer potency against bladder cancers.